The Anatomical and Physiological Basis of the Mongolian Khuumii - Tsagaankhuu, Rentsendorj; Palamdorj, Ganchimeg; Luvsandagva, Byambasuren; Dagdanbazar, Nyamdorj (Central Asian Journal of Medical Sciences, 2023)
Objectives: In order to examine each variety of khuumii used by Mongolians, this study compares the anatomical structures involved in the development of khuumii as well as the characteristics and patterns of their functioning. Methods: 50 people between the ages of 18 and 60 were chosen for the cross-sectional study, using a non-random sampling procedure. Statistical analysis was performed using SPSS23 software using questionnaires, X-ray, endoscopy, and acoustic analysis. Results: During the formation of khuumii sound, thoracic cavity, diaphragm, and lungs regulate the intensity of the air reaching the vocal folds, exert pressure on the airways and vibrate the sound waves through air flows passing through the larynx and vocal folds. The mouth-nose cavity as well as the pharynx are responsible for resonating the sound. Khuumii increases the workload of the cardiovascular system by 70-80%. Furthermore, the sound frequency is 2-4 times higher than that of normal speech, and sound volume is 0.5-1 times higher. 95.3% of throat singers do not have a sore throat, 88.4% do not experience heavy breathing, and 74.1% have no hoarseness. Conclusion: The Mongolian throat singing khuumii, including mixed voices and multivoice, iss related to the presence of dual vibration sound sources. Its high overtone form of singing (isgeree khuumii) is related to stenosis at the resonance chambers initiation site (ventricular folds level).